PENERAPAAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) UNTUK MENINGKATKAN HASIL BELAJAR P.KNSISWA KELAS V SDN 001 BAGANBATU - Endri '; Zariul Antosa; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study background by lower results in student learning in class V SDN 001 Bagan Batu. Of the 30 students only 13 people who reached the KKM while 17 people are still not KKM is 75. It is necessary for the improvement of learning by applying the cooperative learning model type STAD. This research is a class act done in class V SDN 001 Batu Bagan. This study aims to improve learning outcomes P.Kn siswa class V SDN 001 Bagan Batu. Improvement of learning is done by applying cooperative learning model STAD, the learning is done through teamwork with members of a heterogeneous group and end with the implementation of the quiz. This study is classroom action research conducted by two cycles of the four meetings. The research instrument consists of a data collector in the form of observation sheet activities as well as teacher and student achievement test tool. Research data processing is done by a statistical technique using Microsoft Excel. Based on the data processing research found that the application of cooperative learning model STAD can increase the activity of teachers by 75% in the first cycle and activity of students 67.86% with an average value of student learning outcomes adalah71,83. In cycle two percentage teacher activity increased to 92.86% and 85.71% of student activity becomes. The increased activity of teachers and students has been accompanied by increased student learning outcomes be 78. Based on data analysis research note that the application of cooperative learning model STAD can improve learning outcomes P.Kn fifth grade students of SDN 001 Batu Bagan. Thus the research hypothesis that the application of cooperative learning model STAD can improve learning outcomes P.Kn fifth grade students of SDN 001 Bagan Batu proven. Key Words: Student Team Acseleration Divissions cooperative, learning outcomes P.Kn